Managing the Pancasila Student Profile to Strengthen Religious Character in Elementary Schools - Abdul Razak (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The growing influence of globalization and digitalization has intensified moral and religious challenges in elementary education, requiring schools to adopt more systematic approaches to character formation . In Indonesia, the Pancasila Student Profile (P5) has been introduced as a national framework to strengthen students’ character, particularly religious values, within the Merdeka Curriculum . However, existing studies indicate that character education initiatives often remain symbolic when they are not supported by effective school management.This study examines how educational management practices shape the implementation of the Pancasila Student Profile in strengthening students’ religious character in a public elementary school. Employing a qualitative case study design, data were collected through in-depth interviews, observations, and document analysis involving school leaders, teachers, and students (50%). The findings reveal that coherent planning, clear organizational structures, consistent implementation through daily routines and project-based learning, and reflective evaluation play a critical role in facilitating the internalization of religious character. Leadership commitment, teacher exemplarity, and parental involvement further support program sustainability.The study concludes that strengthening religious character through the Pancasila Student Profile is not merely a curricular effort but an organizational achievement shaped by school management practices. These findings contribute to educational management and character education literature by demonstrating how national character policy can be operationalized effectively at the school level.